2008
DOI: 10.1159/000165382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Gastric Cancer with Metastasis to the Lymph Node along the Superior Mesenteric Vein (14v)

Abstract: Aim: We investigated the clinical significance of metastasis to the lymph node (LN) along the superior mesenteric vein (14v) in gastric cancer. Methods: A retrospective study of 2,513 gastrectomy patients with a 14v dissection was done using the Ganken Igan Database. Results: The incidence of 14v metastasis correlated with tumor location, depth of tumor invasion, regional LN metastases, peritoneal metastasis, peritoneal cytology-positive, hepatic metastasis and postoperative recurrence (p < 0.01). Metastases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
(20 reference statements)
2
27
0
Order By: Relevance
“…The frequency of 14v metastasis has been reported to be between 10 and 20 per cent in advanced-stage distal gastric cancer 6,15 . It has been suggested that some patients with 14v metastasis may derive benefit from 14v dissection, and it is important to identify such patients accurately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of 14v metastasis has been reported to be between 10 and 20 per cent in advanced-stage distal gastric cancer 6,15 . It has been suggested that some patients with 14v metastasis may derive benefit from 14v dissection, and it is important to identify such patients accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The need for 14v dissection is based on the anatomical location in the lymphatic drainage pathway and on the frequency of 14v metastasis reported in several Japanese studies 4,5 . Although the incidence of 14v metastasis is very low in early-stage gastric cancer at 1·3 per cent, it rises to 19·7 per cent in advanced gastric cancer 6 . The clinical significance and prognostic value of 14v metastasis has been investigated in Japanese studies, but has not been analysed worldwide.…”
Section: Introductionmentioning
confidence: 90%
“…(35) The clinical significance of lymph node no.14v metastasis was evaluated in a large-scaled Japanese study, and the prognostic impact of 14v lymph node metastasis seems to be strong. (36) The authors suggested that the prognosis of patients with 14v metastasis was similar to those with systemic metastasis and only some patients had a chance to be cured by 14v dissection. In a retrospective Korean study, authors suggested a subgroup of gastric cancer getting merits from 14v dissection.…”
Section: Surgical Treatment Of Advanced Gastric Cancermentioning
confidence: 99%
“…6 metastasis is a pivotal risk factor for a No. 14v metastasis [9]. In addition to the presented case, previous studies demonstrate that there is a lymphatic pathway from the infra-pyloric area to around the mesenteric superior vein/artery.…”
Section: Discussionmentioning
confidence: 51%